Composite current collector and preparation method thereof
By introducing insertion metal layer and rare earth elements into the composite aluminum foil to form an alloy diffusion layer, the problems of poor bonding strength and corrosion of the composite film are solved, the bonding strength and tensile strength of the coating are improved, and the overall performance of the composite film is enhanced.
Patent Information
- Application Number
- CN202411394796.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The metal compound produced by the aluminum-plated composite film prepared by vacuum evaporation technology in the existing composite aluminum foil reacts with aluminum at high temperature, resulting in poor binding force between polymer substrate and metal plating, which is easy to fall off, especially after multiple evaporations. The gaps between the layers cause corrosion, affecting its service life.
Using vacuum evaporation technology to form a multi-layer aluminum plating layer on the base film, and an intercalated metal layer, such as manganese, rhenium, erbium, gadolinium and other metals, is introduced to form an alloy diffusion layer to enhance the bonding force and tensile resistance between the aluminum layers. Strength, improve impurity distribution and grain refinement through rare earth elements, and improve corrosion resistance.
It effectively improves the bonding strength, tensile strength and corrosion resistance of the metal plating layer, reduces the delamination and shedding of the plating during pulling and rolling, and enhances the overall performance of the composite film.
Smart Images

Figure CN119297289A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a composite current collector and a preparation method thereof. Background Art
[0002] Composite aluminum foil is a "sandwich" structure formed by plating 1 micron aluminum on the upper and lower surfaces of a 6-micron PET base film through a vacuum evaporation process. The mainstream process of composite aluminum foil is evaporation, which uses vacuum evaporation coating to feed aluminum wire into a high-temperature evaporation boat. Under the electric heating method (heated to 1000-1200°C), solid aluminum is converted into gaseous aluminum. Oxygen is simultaneously introduced into the aluminum vapor diffusion channel to react with aluminum molecules to generate metal compounds, which are deposited on the surface of the substrate to form a 5-15nm dense and corrosion-resistant auxiliary layer. Despite this, the aluminum-plated composite film prepared by the evaporation process has good metal properties. However, compared with traditional aluminum foil, this composite film prepared based on physical vapor deposition has poor bonding between its polymer substrate and the metal coating, which makes the metal coating easy to fall off, and the gaps between the aluminum layers make it easy to corrode. Especially in the case of multiple vapor deposition, the atomic gaps between the aluminum layers will lead to low bonding strength. In the actual production process, the bonding strength between the several aluminum layers located in the middle of the conductive layer is lower than that of other layers. This causes the coating to be delaminated and fall off when the composite film is pulled or rolled, seriously affecting its use. Summary of the invention
[0003] In order to improve the situation that the coating layer delamination and shedding occurs when the composite film is pulled or rolled, the present invention proposes a composite current collector. The above purpose can be achieved by the following technical solution implementation method:
[0004] A composite current collector, comprising:
[0005] A base film, wherein the base film is made of a polymer material;
[0006] A conductive layer, the conductive layer is arranged on the base film; the conductive layer comprises a first aluminum layer, an alloy diffusion layer, and a second aluminum layer in sequence in a direction away from the base film;
[0007] The alloy diffusion layer includes multiple layers of alternately stacked inserted metal layers and aluminum coatings; each inserted metal layer includes at least one coating formed by an additional element, and the additional element includes at least one metal element having a metal diffusion rate greater than that of aluminum.
[0008] Optionally, the additional element includes at least one rare earth element.
[0009] Optionally, the additional element includes at least one of rhenium, erbium, gadolinium and manganese.
[0010] Optionally, the alloy diffusion layer includes at least three inserted metal layers.
[0011] Optionally, the thickness of the inserted metal layer in the alloy diffusion layer is 40-70 nanometers.
[0012] Optionally, as the distance between the inserted metal layer and the first aluminum layer increases, the thickness of the inserted metal layer first increases and then decreases.
[0013] Optionally, the thickness of each aluminum coating layer in the alloy diffusion layer is 40-70 nm.
[0014] Optionally, the first aluminum layer and the second aluminum layer are both formed by stacking multiple aluminum plating layers; the thickness ratio of the first aluminum layer to the second aluminum layer is 2 to 2.6:1;
[0015] Optionally, the first aluminum layer comprises 5 to 15 aluminum plating layers, and the thickness of each aluminum plating layer is 50 to 70 nm;
[0016] The second aluminum layer comprises 1 to 8 layers, and the thickness of each aluminum coating layer is 40-55 nm.
[0017] Optionally, an aluminum oxide layer is provided between the base film and the conductive layer.
[0018] A method for preparing a composite current collector comprises the following steps:
[0019] Step 1) depositing multiple layers of aluminum coating on the base film by vacuum evaporation to form a first aluminum layer;
[0020] Step 2) alternately depositing multiple layers of inserted metal layers and aluminum coating layers on the first aluminum layer by vacuum evaporation to form an alloy diffusion layer;
[0021] Step 3) Depositing multiple layers of aluminum coating on the alloy diffusion layer by vacuum evaporation to form a second aluminum layer.
[0022] Optionally, the temperature of the vacuum evaporation aluminum coating is 1000-1200°C, 10 -3 ~5*10 -2 Pa; and / or
[0023] In the step 2), erbium is used as an additive element to prepare the inserted metal layer, and the vacuum evaporation temperature is 1000-1200° C. and the vacuum degree is 10 -3 ~5*10 -2 Pa; and / or
[0024] In the step 2), gadolinium is used as an additive element to prepare an inserted metal layer, and the vacuum evaporation temperature is 1500-1700° C. and the vacuum degree is 10 -3 ~5*10 -2 Pa; and / or
[0025] In the step 2), manganese is used as an additive element to prepare the inserted metal layer, and the vacuum evaporation temperature is 1400-1600° C. and the vacuum degree is 10 -3 ~5*10 -2 Pa.
[0026] The technical solution of the present invention has the following advantages:
[0027] The present invention introduces a variety of inserted metals into the original composite aluminum current collector. The metal diffusion rate of the selected inserted metals is greater than that of aluminum, such as manganese and rare earth metals, which can first occupy active sites and inhibit the growth of aluminum crystals, so that the intermetallic compounds formed by these inserted metals and aluminum are distributed in spherical and short rod shapes at the grain boundaries or within the boundaries, and a large number of dislocations are distributed in the metal structure, thereby improving the bonding strength and tensile strength of the metal coating and also improving the corrosion resistance.
[0028] The present invention introduces a variety of inserted metals into the middle layers to construct crystal dislocations, increase the resistance to dislocation slip, thereby improving the tensile strength of the current collector and reducing the delamination and shedding of the coating during rolling. Rare earth has the effect of reducing the content of hydrogen, oxygen and sulfur in aluminum and aluminum alloys, which helps to better remove harmful impurities, refine impurities or change their morphology, so that the grains are refined and evenly distributed; it can eliminate the coarse block phase distributed in the original crystal and form a spherical phase, so that the strip and broken block compounds at the grain boundary are significantly reduced. Under normal circumstances, the atomic radius of rare earth is larger than the atomic radius of aluminum, and its properties are relatively active. It is very easy to fill the surface defects of the alloy phase when melted in aluminum liquid, so that the surface tension on the interface between the new and old phases is reduced, and the growth rate of the crystal nucleus is increased; at the same time, it can also form a surface active film between the grains and the molten liquid to prevent the generated grains from growing and refine the alloy structure; in addition, the compound formed by aluminum and rare earth has a large increase in the number of crystal nuclei during metal crystallization, which also refines the alloy structure.
[0029] The thickness of the inserted metal layer introduced in the present invention shows a certain variation trend from the base film to the surface of the aluminum layer, so as to improve the consistency of the bonding strength of the multi-layer aluminum layer in the thickness direction, and further improve the problem of uneven internal and external stress caused by the later pole piece rolling and use in the battery;
[0030] The inserted metal layer introduced by the present invention can be selected from a variety of metals to introduce the performance advantages of multiple metals, while improving the tensile strength, corrosion resistance and thermal conductivity of the current collector. Compared with introducing other metal layers between each aluminum layer, this solution can reduce the impact of other metals on the square resistance of the current collector, ensure the conductivity of the current collector, and reduce the repeated replacement of evaporation materials in the process preparation, reducing the cleaning of the evaporation equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 It is a schematic diagram of the current collector structure of the present invention. DETAILED DESCRIPTION
[0033] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0034] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0035] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0036] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0037] In the prior art, 15 to 25 layers of aluminum are generally plated on the aluminum oxide layer to make the performance index reach the process setting value. The present invention introduces a variety of inserted metals into the original composite aluminum current collector by vacuum coating. The metal diffusion rate of the selected inserted metal is greater than that of aluminum. For example, rare earth metals are selected to occupy the active sites first and inhibit the growth of aluminum crystals, so that the intermetallic compounds formed by these inserted metals and aluminum are distributed in the shape of spheres and short rods at the grain boundaries or within the boundaries, and there are a large number of dislocations in the metal structure, thereby improving the bonding strength and tensile strength of the metal coating, and also improving the corrosion resistance.
[0038] Example 1
[0039] Compared with the existing aluminum coating, this embodiment coats a single layer of manganese metal and aluminum between layers 6-7, 7-8, and 8-9 to form an alloy coating. The specific steps are as follows:
[0040] The base film is fixed to the winding trolley, and the film is retracted and released, and then the tension is adjusted. The film release end is 120N, and the rewinding end is 100N. After the winding trolley enters the evaporation chamber, it is vacuumed to 5*10 -3 Pa, start the winding trolley, control the speed at 280-300m / min, heat the evaporation boat and feed the aluminum wire at a speed of 300-350mm / min, start the oxygen intake, and apply aluminum oxide primer on the surface of the base film. The vacuum degree is controlled at 5*10 -2 Pa. Then break the vacuum and plate a layer of aluminum in the same way, heating temperature is 1000-1200℃. After 5 layers of aluminum plating are completed, replace the metal wire and plate a layer of manganese metal under the same conditions, heating temperature is 1400-1600℃. The 8th layer is plated with aluminum, the 9th layer is plated with manganese metal, the 10th layer is plated with aluminum, and the 11th layer is plated with manganese metal. Then aluminum is plated until the surface resistance is about 40mΩ·□. Samples are taken for each coating to test the coating adhesion. The test calculation shows that the average coating thickness is about 53nm and the aluminum adhesion is about 162mg / m 2 , the amount of manganese attached is 440mg / m 2 The current collector structure is obtained as Figure 1 As shown, an aluminum oxide layer 2, a first aluminum layer 3, an alloy diffusion layer 4, and a second aluminum layer 5 are sequentially arranged on a base film 1, and the alloy diffusion layer 4 is formed by alternately arranging an inserted metal layer 41 and an aluminum plating layer 42.
[0041] Example 2
[0042] Compared with the existing aluminum coating, this embodiment coats a single layer of rhenium metal and aluminum between the 6th and 7th layers, the 7th and 8th layers, and the 8th and 9th layers to form an alloy coating. The specific steps are as follows:
[0043] The base film is fixed to the winding trolley, and the film is retracted and released, and then the tension is adjusted. The film release end is 120N, and the rewinding end is 100N. After the winding trolley enters the evaporation chamber, it is vacuumed to 5*10 -3 Pa, start the winding trolley, control the speed at 280-300m / min, heat the evaporation boat and feed the aluminum wire at a speed of 300-350mm / min, start the oxygen intake, and apply aluminum oxide primer on the surface of the base film. The vacuum degree is controlled at 5*10 -2Pa. Then break the vacuum and plate a layer of aluminum in the same way, the heating temperature is 1000-1200℃, after the positive and negative aluminum plating is completed 5 times, replace the metal wire, and plate a layer of rhenium metal under the same conditions, the heating temperature is 3200-3700℃. The 8th layer is plated with aluminum, the 9th layer is plated with rhenium metal, the 10th layer is plated with aluminum, and the 11th layer is plated with rhenium metal. Then continue to plate aluminum until the surface resistance is about 40mΩ·□. Samples are taken for each coating to test the coating adhesion. The test calculation shows that the average coating thickness is about 53nm, and the aluminum adhesion is about 162mg / m 2 The amount of rhenium attached is about 1260 mg / m 2 .
[0044] Example 3
[0045] Compared with the existing aluminum coating, this embodiment coats a single layer of erbium metal and aluminum between the 6th and 7th layers, the 7th and 8th layers, and the 8th and 9th layers to form an alloy coating. The specific steps are as follows:
[0046] The base film is fixed to the winding trolley, and the film is retracted and released, and then the tension is adjusted. The film release end is 120N, and the rewinding end is 100N. After the winding trolley enters the evaporation chamber, it is vacuumed to 5*10 -3 Pa, start the winding trolley, control the speed at 280-300m / min, heat the evaporation boat and feed the aluminum wire at a speed of 300-350mm / min, start the oxygen intake, and apply aluminum oxide primer on the surface of the base film. The vacuum degree is controlled at 5*10 -2 Pa. Then break the vacuum and plate a layer of aluminum in the same way, heating the temperature to 1000-1200℃. After 5 layers of aluminum plating on both sides, replace the metal wire and plate a layer of erbium metal under the same conditions, heating the temperature to 1700-2000℃. The 8th layer is plated with aluminum, the 9th layer is plated with erbium metal, the 10th layer is plated with aluminum, and the 11th layer is plated with erbium metal. Then continue to plate aluminum until the surface resistance is about 40mΩ·□. Samples are taken for each coating to test the coating adhesion. The test calculation shows that the average coating thickness is about 60nm and the aluminum adhesion is about 162mg / m 2 The amount of erbium attached is about 530mg / m 2 .
[0047] Example 4
[0048] Compared with the existing aluminum coating, this embodiment coats a single layer of gadolinium metal and aluminum between the 6th and 7th layers, the 7th and 8th layers, and the 8th and 9th layers to form an alloy coating. The specific steps are as follows:
[0049] The base film is fixed to the winding trolley, and the film is retracted and released, and then the tension is adjusted. The film release end is 120N, and the rewinding end is 100N. After the winding trolley enters the evaporation chamber, it is vacuumed to 5*10 -3Pa, start the winding trolley, control the speed at 280-300m / min, heat the evaporation boat and feed the aluminum wire at a speed of 300-350mm / min, start the oxygen intake, and apply aluminum oxide primer on the surface of the base film. The vacuum degree is controlled at 5*10 -2 Pa. Then break the vacuum and plate a layer of aluminum in the same way, heating the temperature to 1000-1200℃. After 5 layers of aluminum plating on both sides, replace the metal wire and plate a layer of gadolinium metal under the same conditions, heating the temperature to 1500-1700℃. The 8th layer is plated with aluminum, the 9th layer is plated with gadolinium metal, the 10th layer is plated with aluminum, and the 11th layer is plated with gadolinium metal. Then continue to plate aluminum until the surface resistance is about 40mΩ·□. Samples are taken for each coating to test the coating adhesion. The test calculation shows that the average coating thickness is about 52nm and the aluminum adhesion is about 162mg / m 2 The amount of gadolinium attached is about 475 mg / m 2 .
[0050] Example 5
[0051] Compared with the existing aluminum coating, this embodiment coats a single layer of manganese metal between the 6th and 7th layers and the 8th and 9th layers, wherein the 7th and 8th layers are coated with five layers of erbium metal and aluminum to form an alloy coating. The specific steps are as follows:
[0052] The base film is fixed to the winding trolley, and the film is retracted and released, and then the tension is adjusted. The film release end is 120N, and the rewinding end is 100N. After the winding trolley enters the evaporation chamber, it is vacuumed to 5*10 -3 Pa, start the winding trolley, control the speed at 280-300m / min, heat the evaporation boat and feed the aluminum wire at a speed of 300-350mm / min, start the oxygen intake, and apply aluminum oxide primer on the surface of the base film. The vacuum degree is controlled at 5*10 -2 Pa. Then break the vacuum and plate a layer of aluminum in the same way, heating the temperature to 1000-1200℃. After 5 layers of aluminum are plated on both sides, replace the metal wire and plate a layer of manganese metal under the same conditions, heating the temperature to 1400-1600℃. Plate the 8th layer of aluminum, then plate 5 layers of the second metal in succession, the 14th layer of aluminum, the 15th layer of the second metal, and then continue to plate aluminum until the surface resistance is about 40mΩ·□. Samples are taken for each coating to test the coating adhesion. The test calculation shows that the average coating thickness is about 60nm and the aluminum adhesion is about 162mg / m 2 The amount of erbium attached is about 530mg / m 2 The amount of gadolinium attached is about 475 mg / m 2 , the amount of manganese attached is 440mg / m 2 .
[0053] Example 6
[0054] Compared with the existing aluminum coating, this embodiment coats a single layer of manganese metal between the 6th and 7th layers and the 8th and 9th layers, wherein the 7th and 8th layers are coated with five layers of erbium metal and aluminum to form an alloy coating. The specific steps are as follows:
[0055] The base film is fixed to the winding trolley, and the film is retracted and released, and then the tension is adjusted. The film release end is 120N, and the rewinding end is 100N. After the winding trolley enters the evaporation chamber, it is vacuumed to 5*10 -3 Pa, start the winding trolley, control the speed at 280-300m / min, heat the evaporation boat and feed the aluminum wire at a speed of 300-350mm / min, start the oxygen intake, and apply aluminum oxide primer on the surface of the base film. The vacuum degree is controlled at 5*10 -2 Pa. Then break the vacuum and plate a layer of aluminum in the same way, with a heating temperature of 1000-1200℃. After 5 layers of aluminum plating on both sides, replace the metal wire and plate a layer of manganese metal under the same conditions, with a heating temperature of 1400-1600℃ (manganese). Plate the 8th layer of aluminum, and then continuously plate 5 layers of erbium metal, with a heating temperature of 1700-2000℃. Plate the 14th layer of aluminum, the 15th layer of manganese metal, and then continue to plate aluminum until the surface resistance is about 40mΩ·□. Samples are taken for each coating to test the coating adhesion. The test calculation shows that the average coating thickness is about 53nm, and the aluminum adhesion is about 162mg / m 2 The amount of erbium attached is about 530mg / m 2 , the amount of manganese attached is 440mg / m 2 .
[0056] Example 7
[0057] Compared with the existing aluminum coating, this embodiment coats a single layer of manganese metal between the 6th and 7th layers and the 8th and 9th layers, wherein the 7th and 8th layers are coated with five layers of gadolinium metal and aluminum to form an alloy coating. The specific steps are as follows:
[0058] The base film is fixed to the winding trolley, and the film is retracted and released, and then the tension is adjusted. The film release end is 120N, and the rewinding end is 100N. After the winding trolley enters the evaporation chamber, it is vacuumed to 5*10 -3 Pa, start the winding trolley, control the speed at 280-300m / min, heat the evaporation boat and feed the aluminum wire at a speed of 300-350mm / min, start the oxygen intake, and apply aluminum oxide primer on the surface of the base film. The vacuum degree is controlled at 5*10 -2Pa. Then break the vacuum and plate a layer of aluminum in the same way, with a heating temperature of 1000-1200℃. After 5 layers of aluminum plating on both sides, replace the metal wire and plate a layer of manganese metal under the same conditions, with a heating temperature of 1400-1600℃ (manganese). Plate the 8th layer of aluminum, and then continuously plate 5 layers of gadolinium metal, with a heating temperature of 1500-1700℃. Plate the 14th layer of aluminum, the 15th layer of manganese metal, and then continue to plate aluminum until the surface resistance is about 40mΩ·□. Samples are taken for each coating to test the coating adhesion. The test calculation shows that the average coating thickness is about 53nm, and the aluminum adhesion is about 162mg / m 2 The amount of gadolinium attached is about 475 mg / m 2 , the amount of manganese attached is 440mg / m 2 .
[0059] Example 8
[0060] Compared with the existing aluminum coating, this embodiment coats a single layer of manganese metal between the 6th and 7th layers and the 8th and 9th layers, wherein two metal single layers of erbium and gadolinium (erbium is plated first and then gadolinium) are plated between the 7th and 8th layers to form an alloy coating with aluminum. The specific steps are as follows:
[0061] The base film is fixed to the winding trolley, and the film is retracted and released, and then the tension is adjusted. The film release end is 120N, and the rewinding end is 100N. After the winding trolley enters the evaporation chamber, it is vacuumed to 5*10 -3 Pa, start the winding trolley, control the speed at 280-300m / min, heat the evaporation boat and feed the aluminum wire at a speed of 300-350mm / min, start the oxygen intake, and apply aluminum oxide primer on the surface of the base film. The vacuum degree is controlled at 5*10 -2 Pa. Then break the vacuum and plate a layer of aluminum in the same way, with a heating temperature of 1000-1200℃. After 5 layers of aluminum plating on both sides, replace the metal wire and plate manganese metal under the same conditions, with a heating temperature of 1400-1600℃. The 8th layer is plated with aluminum, and the 9th and 10th layers are plated with erbium and gadolinium. Erbium is plated first and then gadolinium. The heating temperature is 1700-2000℃ (erbium) / 1500-1700℃ (gadolinium) / 1400-1600℃. The 11th layer is plated with aluminum, and the 12th layer is plated with manganese metal. After that, aluminum is plated until the surface resistance is about 40mΩ·□. Samples are taken for each coating to test the coating adhesion. The test calculation shows that the average coating thickness is about 60nm, and the aluminum adhesion is about 162mg / m 2 The amount of erbium attached is about 530mg / m 2 The amount of gadolinium attached is about 475 mg / m 2 , the amount of manganese attached is 440mg / m 2 .
[0062] Example 9
[0063] Compared with the existing aluminum coating, this embodiment coats a single layer of manganese metal between the 6th and 7th layers and the 8th and 9th layers, wherein erbium, gadolinium, rhenium and aluminum are plated between the original 7th and 8th layers to form an alloy coating. The specific steps are as follows:
[0064] The base film is fixed to the winding trolley, and the film is retracted and released, and then the tension is adjusted. The film release end is 120N, and the rewinding end is 100N. After the winding trolley enters the evaporation chamber, it is vacuumed to 5*10 -3 Pa, start the winding trolley, control the speed at 280-300m / min, heat the evaporation boat and feed the aluminum wire at a speed of 300-350mm / min, start the oxygen intake, and apply aluminum oxide primer on the surface of the base film. The vacuum degree is controlled at 5*10 -2 Pa. Then break the vacuum and plate a layer of aluminum in the same way, heating the temperature to 1000-1200℃. After 5 layers of aluminum plating on both sides, replace the metal wire and plate a layer of manganese metal under the same conditions, heating the temperature to 1400-1600℃. The 8th layer is plated with aluminum, the 9th / 10th / 11th layer is plated with erbium, gadolinium, and rhenium respectively, the 12th layer is plated with aluminum, and the 13th layer is plated with manganese metal. Then aluminum is plated until the surface resistance is about 40mΩ·□. Samples are taken for each coating to test the coating adhesion. The test calculation shows that the average coating thickness is about 60nm, and the aluminum adhesion is about 162mg / m 2 The amount of erbium attached is about 530mg / m 2 The amount of gadolinium attached is about 475 mg / m 2 The amount of rhenium attached is about 1260 mg / m 2 , the amount of manganese attached is 440mg / m 2 .
[0065] Comparative Example 1
[0066] Compared with Example 1, this comparative example is an original aluminum-plated sample without adding a second metal, and the specific steps are as follows:
[0067] The base film is fixed to the winding trolley, and the film is retracted and released, and then the tension is adjusted. The film release end is 120N, and the rewinding end is 100N. After the winding trolley enters the evaporation chamber, it is vacuumed to 5*10 -3 Pa, start the winding trolley, control the speed at 280-300m / min, heat the evaporation boat and feed the aluminum wire at a speed of 300-350mm / min, start the oxygen intake, and apply aluminum oxide primer on the surface of the base film. The vacuum degree is controlled at 5*10 -2Pa. Then, the vacuum was broken and a layer of aluminum was plated in the same way. The heating temperature was 1000-1200℃, and aluminum was plated until the surface resistance was about 40mΩ·□. Samples were taken for each coating to test the coating adhesion. The average coating thickness was calculated to be about 53nm, and the aluminum adhesion was about 162mg / m 2 .
[0068] Comparative Example 2
[0069] Compared with Example 1, in this comparative example, a single layer of manganese metal is plated between the aluminum oxide layers -1, 1-2, and 2-3, and the specific steps are as follows:
[0070] The base film is fixed to the winding trolley, and the film is retracted and released, and then the tension is adjusted. The film release end is 120N, and the rewinding end is 100N. After the winding trolley enters the evaporation chamber, it is vacuumed to 5*10 -3 Pa, start the winding trolley, control the speed at 280-300m / min, heat the evaporation boat and feed the aluminum wire at a speed of 300-350mm / min, start the oxygen intake, and apply aluminum oxide primer on the surface of the base film. The vacuum degree is controlled at 5*10 -2 Pa. Then break the vacuum and plate a layer of manganese metal in the same way, heating temperature 1400-1600℃. Then plate a layer of aluminum, a layer of manganese, and plate aluminum until the surface resistance is about 40mΩ·□ after plating 3 layers of manganese. Samples are taken for each coating to test the coating adhesion. The test calculation shows that the average coating thickness is about 53nm, the aluminum adhesion is about 162mg / m2, and the manganese adhesion is 440mg / m 2 .
[0071] The meanings of the number of layers such as 1 layer, 7 layers, 8 layers, etc. mentioned in the above embodiments are: the aluminum coating layer closest to the base film is counted as 1 layer, and each aluminum coating layer is counted in sequence according to the distance from the base film.
[0072] Test Case
[0073] The surface square resistance, tensile strength MD, tensile strength TD, peel strength and thickness of the composite current collector material were tested. The test results are shown in Table 1. The specific test method is as follows:
[0074] Surface square resistance: The square resistance is measured by a four-probe resistivity tester. The number of square resistance tests is determined according to the lateral width of the product, and one point is tested every 100mm. Other requirements are tested according to the methods specified in GBIT 22638.6-2016.
[0075] Tensile strength: The room temperature tensile strength and elongation at break of the composite aluminum foil were measured using an electronic universal material testing machine. The test conditions were: gauge length 10 mm, tensile speed 100 mm / nin, width 15 mm. Other requirements were measured according to the method specified in GB / T 1040.3-2006.
[0076] Peel strength: Take a test sample with a size of 15*100mm, stick the 3M-9080A-15mm tape on a stainless steel plate, then stick the test sample evenly on the double-sided tape, use a 2kg standard small roller to squeeze it back and forth twice, then stick the 3M-9080A-14mm tape on the surface of the sample, use a 2kg standard small roller to squeeze it back and forth twice, then take the pressed sample to a tensile testing machine and stretch it 180° at a speed of 100mm / min and a width of 14mm. The maximum value is taken.
[0077] Table 1 Physical data of composite membranes in Example
[0078]
[0079] By comparing Examples 1-4 with Comparative Example 1, it can be seen that inserting a second metal into the original aluminum layer of the present invention can effectively improve the tensile strength and peel strength of the composite aluminum current collector, and it can be seen that the dislocation distribution of multiple metals strengthens the bonding between the metal layers. By comparing each embodiment with Comparative Example 2, it can be seen that the bonding strength between the newly added metal and the aluminum oxide base layer is poor, so it is necessary to plate at least one layer of aluminum on the base layer before applying the second metal coating;
[0080] In Examples 8 and 9, the types of added metals are expanded to 2 and 3, and the dislocation effect between different metals is further enhanced. At the same time, due to the different radii of metal atoms, the interlayer defect positions are filled with other small radius atoms, which prevents the generated grains from growing, refines the alloy structure, and further improves the bonding strength between metal layers.
[0081] Obviously, the above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from them are still within the protection scope of the invention.
Claims
1. A composite current collector, characterized in that: include: A base film, wherein the base film is made of a polymer material; A conductive layer, the conductive layer is arranged on the base film; the conductive layer comprises a first aluminum layer, an alloy diffusion layer, and a second aluminum layer in sequence in a direction away from the base film; The alloy diffusion layer includes multiple layers of alternately stacked inserted metal layers and aluminum coatings; each inserted metal layer includes at least one coating formed by an additional element, and the additional element includes at least one metal element having a metal diffusion rate greater than that of aluminum.
2. The composite current collector according to claim 1, characterized in that: The additional element includes at least one rare earth element.
3. The composite current collector according to claim 1 or 2, characterized in that: The additional element includes at least one of rhenium, erbium, gadolinium and manganese.
4. The composite current collector according to claim 1, characterized in that: The alloy diffusion layer includes at least three inserted metal layers.
5. The composite current collector according to claim 1, characterized in that: The thickness of the inserted metal layer in the alloy diffusion layer is 40-70 nanometers; Preferably, as the distance between the inserted metal layer and the first aluminum layer increases, the thickness of the inserted metal layer first increases and then decreases.
6. The composite current collector according to claim 1, characterized in that: The thickness of each aluminum coating layer in the alloy diffusion layer is 40-70 nm.
7. The composite current collector according to claim 1, characterized in that: The first aluminum layer and the second aluminum layer are both formed by stacking multiple aluminum coatings; the thickness ratio of the first aluminum layer to the second aluminum layer is 2-2.6:1; preferably, the first aluminum layer comprises 5-15 aluminum coatings, and the thickness of each aluminum coating is 50-70 nm; The second aluminum layer comprises 1 to 8 layers, and the thickness of each aluminum coating layer is 40-55 nm.
8. The composite current collector according to any one of claims 1 to 7, characterized in that: An aluminum oxide layer is provided between the base film and the conductive layer.
9. A method for preparing a composite current collector, characterized in that: The steps include: Step 1) depositing multiple layers of aluminum coating on the base film by vacuum evaporation to form a first aluminum layer; Step 2) alternately depositing multiple layers of inserted metal layers and aluminum coating layers on the first aluminum layer by vacuum evaporation to form an alloy diffusion layer; Step 3) Depositing multiple layers of aluminum coating on the alloy diffusion layer by vacuum evaporation to form a second aluminum layer.
10. The method for preparing a composite current collector according to claim 9, characterized in that: The temperature of vacuum evaporation aluminum coating is 1000-1200℃, and the vacuum degree is 10 -3 ~5*10 -2 Pa; and / or In the step 2), erbium is used as an additive element to prepare the inserted metal layer, and the vacuum evaporation temperature is 1000-1200° C. and the vacuum degree is 10 -3 ~5*10 -2 Pa; and / or In the step 2), gadolinium is used as an additive element to prepare an inserted metal layer, and the vacuum evaporation temperature is 1500-1700° C. and the vacuum degree is 10 -3 ~5*10 -2 Pa; and / or In the step 2), manganese is used as an additive element to prepare the inserted metal layer, and the vacuum evaporation temperature is 1400-1600° C. and the vacuum degree is 10 -3 ~5*10 -2 Pa.
Citation Information
Patent Citations
Electrode with a coating, method in production thereof and use of a material
CN102017254A
Improvement method, welding method, machining system, control device, and program product
CN116135398A
Negative current collector, preparation method thereof and lithium ion battery
CN117438589A
Current collector composite membrane, preparation method thereof and battery
CN118207535A
Cited By
Test probe, probe card, and test probe manufacturing method
CN120405195A